Irradiation of sputtered Al-Si-N coatings by pulsed 200 keV C+ ion beam. (December 2018) - Remnev, G.; Tarbokov, V.; Pavlov, S.; Konusov, F.; Zenkin, S.; Musil, J.
Abstract: This paper reports on the effect of the irradiation of Al-Si-N coatings by an intense pulsed ion beam. The Al-Si-N coating was deposited on a steel substrate by a reactive magnetron sputtering. The Al-Si-N coating with a high silicon content (30 at.%) was irradiated by a high-intense pulsed C + ion beam. It was shown that metastable growth defects (GDs) created in the Al-Si-N coating during deposition can be healed up by its post-deposition irradiation using several pulses (1 and 10) of C + ions with energy Ei  = 200 keV, ion current density is  = 7 A/cm 2, pulse duration tp  = 110 ns and radiation dose 2 MGy. The reduction in deposition-induced GD density results in an increased transmittance of the Al-Si-N coatings. Highlights: Al-Si-N coating irradiation with 200 keV C+ ion beam. Healing-up of growth defects. Generation of radiation defects. Light transmittance through Al-Si-N coating.